Modified Stark's (Misgav Ladach) caesarean section: 15 – year experience of the own techniques of caesarean section. (April 2020) - Habek, Dubravko; Cerovac, Anis; Luetić, Ana; Marton, Ingrid; Prka, Matija; Kulaš, Tomislav; Ujević, Boris
Abstract: Objective: A 15-year-experience of the personal modification of Misgav Ladach (ML) caesarean section in relation to the Dörffler method. Study design: A retrospective clinical randomized observational study included 822 transperitoneal cesarean sections: 557 were performed via modified ML (without bladder catheterization, small transverse fascial incision with muscular stretching and non-preparation of vesicouterine plica) vs . 265 Dörffler (Pfannenstiel – Kerr) method. Results: Perioperative and postoperative complications were significantly more frequent in the Dörffler method (p < 0.0005) (perioperative hemorrhage, more frequent adhesions, plastic peritonitis in repeated caesarean sections, as well as two bladder lesions). Postoperative febrility, dehiscence and wound seroma were more frequent in the first study group (p < 0.0005). More frequent paralytic ileus, uroinfections and bladder atony, which we did not observe in our own technique (p < 0.0005). The use of antibiotics and analgesics was prolonged until the fifth postoperative day in the first group compared to the second group where it was reduced to only 10 % on the second day (p < 0.0005). Also, the incidence of anemia and the need for blood transfusions were higher in the first study group, as well as the need for revision behind caesarean section and two hysterectomies due to massive postoperative intraperitoneal and retroperitoneal bleeding (p < 0.0005). Conclusion: Our fifteen-year study highlighted the importance of our own published modified ML caesarean section in minimizing technique of surgery and the reduction of perioperative morbidity and significantly faster recovery of operated patients in the current era of enormous caesarean section increase.